Islamic Character Education and Nationalism Insight of Students in the Era of Industry 4.0 - Purwanto, Yedi (International Journal of Psychosocial Rehabilitation, 2020)
Islamic Character Education and national insight in the industrial era 4.0 is very important to convey to students in facing the challenges of globalization. This article aims to illustrate the problem of Islamic education and nationality insight in the industrial era 4.0 and to formulate educational management on these issues. Through studying the literature, this qualitative method found that Islam as a religion of peace gives peace to all beings in nature. Second, Islam as a religion rahmatan lil alamin is a moderate religion with regard to aqeedah, sharia, and morals. Third, Islam arranges a peaceful life with communities outside of Islam politely and with respect for human values. The Prophet Muhammad SAW is a plenary figure who must be followed by students in a harmonious life between religion and nationality. Indonesia as a country based on Pancasila guarantees the religious life of its citizens and upholds human values. Therefore the results of this study conclude that Islamic character education and nationalist insight in the industrial era 4.0 are very important.